PENGARUH MOTIVASI DAN BEBAN KERJA TERHADAP KINERJA PRO PLAYER E-SPORT MELALUI KEPUASAN PADA MULTIVERSE E-SPORT DI KOTA MALANG - Darwis, Irman Maulana; Sugito, Pudjo; Natsir, Mokhamad (JURSIMA, 2025)
This study aims to analyze the effect of motivation and workload on pro player e-sport performance through job satisfaction at Multiverse E-sport. The research method uses a quantitative approach with Structural Equation Modeling (SEM) analysis techniques using SmartPLS software. The research sample amounted to 56 e-sport pro players who were taken with saturated sampling technique.The results showed that: (1) Motivation has a positive and significant effect on satisfaction, while workload does not have a significant effect on pro player e-sport satisfaction; (2) Motivation and workload do not have a significant effect on pro player e-sport performance; (3) Satisfaction has a positive and significant effect on pro player e-sport performance; (4) Satisfaction can mediate the effect of motivation on performance, but cannot mediate the effect of workload on pro player e-sport performance at Multiverse E-sport. The implication of this research is the importance of increasing pro player motivation and job satisfaction to improve their performance in the rapidly growing e-sport industry. Future research is recommended to add other variables that can affect the performance of e-sport pro players.